Visual Pollution in Kuwait City – Analytical Study According to The New Environmental Protection Law No. 42 of 2014 - Alqutaifi, Naser Bader (Journal of agricultural, environmental and veterinary sciences, 2022)
Visual pollution is not just a phenomenon, it is a time bomb. The damages caused by this phenomenon can be devastating; Because its manifestations are everywhere. The main aim of this research is to study the manifestations of visual pollution in Kuwait City, as this phenomenon is the most important problem that the city suffers from. In the absence of local studies related to this topic, it was necessary for us to shed light on this phenomenon, in order to enhance the cognitive and environmental awareness among Kuwaitis. In order to combat this phenomenon and improve the aesthetic view of Kuwait City, the current study recommends the need to address visual pollution firmly and seriously, while re-evaluating the law texts related to this topic.
Keywords: Visual Pollution; Environmental Protection Law; Urban Harmony